SOME ASPECTS ON THE BIOLOGY AND POSSIBILITIES OF BIOLOGICAL CONTROL OF Caloptilia sp. DRILLER OF Stylosanthes spp - CHACÓN, PATRICIA; CALDERÓN, MARIO (Revista Colombiana de Entomología, 1979)
Within forage legumes, have been found several promissory Stylosanthes species, which are actually understudied at CIAT within the Tropical Pastures Program. One of the main problems of the Stylosanthes plant, is the stemborer, Caloptilia sp. (Lepidoptera: Gracilariidae), which was found in Colombia at "Carimagua" Experimental Station (Meta) and near of "Quilichao" Experimental Station (Cauca) attacking S. guianensis, S. capitata, S. scabra, S. hamata, S. viscosa, S. angustifolia, S. humilis. The larvae affect mainly the basal portion of the stem making tunnels; the attacked plant shows galls like overgrowings; this damage plus the cattle trampling effect could reduce Stylosanthes plots persistence. This study includes biology aspects, together with the searching of natural enemies and plant resistance and tolerance to the stemborer. The cycle from egg to adult stage takes approximately 87 days, presenting 5 larval instars. The natural enemies found, so far, belong to the order Hymenoptera, the larval parasites Bracon sp. (Braconidae), Anastatoidea sp. (Eupelmidae) and Chelonus sp. (Braconidae). Plant resistance and tolerance studies included two factors: Oviposition preference Larval survival in the stems In both cases significant differences were found between the ecotypes S. guianensis, S. scabra and S. capitata. According to the results S. capitata shows ecotypes with resistance or tolerance characters to stemborer attack.